Management of anti-NMDAR encephalitis with Rituximab: Case report in a Public Hospital of Lima, Peru - Flores Lazo, Lucía B. (2022)
Introduction: Autoimmune encephalitis comprises a wide spectrum of immunological disorders, among them anti-NMDAR is the most frequent. The management of this pathology is complex due to multiple circumstances. Case report: A 19-year-old woman who started a subacute clinical picture with associated behavioral and neurological disorder: hallucinations, heteroaggressiveness, akinetic mutism, epileptic seizures, orofacial dyskinesias, fever and reported transient cardiac arrhythmia. MRI was normal, EEG recorded delta brush waves, CSF and serum studies were negative for secondary causes. Treatment was started with Acyclovir, an anti-crisis drug, and psychotropic drugs, later methylprednisolone with immunoglobulin was started without a satisfactory response. She starts treatment with Rituximab presenting a favorable response. The CSF panel was positive for NMDA. Control with progressive de-escalation of anti-crisis medications and psychotropic drugs is indicated. Conclusion: It is important to recognize early the clinical manifestations of this entity in order to carry out timely management that could improve the prognosis.